Characterisation of chemically exfoliated molybdenum disulfide with ultrasonication - Ooi, Yong Kai (2014)
Molybdenum Disulfide (MoS2) a class of Transition Metal Dichalcogenide (TMD), has garnered renewed interest from researchers after the discovery of graphene. Two-dimensional MoS2 is expected to possess unique properties and have great potential in many areas of study including optoelectronics, photocatalytic applications – due to its direct band gap when monolayers are isolated.